PENGARUH PEMBERIAN JUS NENAS DAN MADU TERHADAP PENURUNAN NYERI MENSTRUASI REMAJA PUTRI DI SMP YP SINGOSARI DELITUA TAHUN 2020 - zuliawati zuliawati (JURNAL ILMIAH DHDT - KEBIDANAN, 2020)
Dysmenorrhea is a medical condition that occurs during menstruation or menstruation that can interfere with activities and requires treatment characterized by pain or tenderness in the abdominal or pelvic area. This study aims to determine the effect of pineapple juice and honey on reducing menstrual pain (dysmenorrhea) in students at YP SINGOSARI DELITUA in 2020. This type of research is a Quasi Experiment with the One-Group Test method. This study aims to obtain information about the effect of pineapple juice and honey on the reduction of menstrual pain (dysmenorrhea) at SMP YP SINGOSARI in 2020. The population used was all 58 students of YP SINGOSARI DELITUA SMP. The sampling technique used incidental sampling, namely 30 people. The variables used are independent variables about the provision of pineapple juice and honey and the dependent variable is about reducing the pain scale. Data analysis using the Wilcoxon test. The results of statistical tests with Wilcoxon, the results obtained ρ value 0.00 < 0.05, then Ho is rejected Ha accepted, which means there is an effect of pineapple juice and honey on reducing menstrual pain for young women at SMP YP Singosari Deli Tua in 2020.